Synergistic effects of high early-life stress exposure and HIV infection on reaction time variability - Sergio, Jordan P.; Kundu, Retina; McIntosh, Roger C.; Palmero, Mabel; Hegde, Rachal R.; de Dios, Marcel A.; Clark, Uraina S. (Frontiers in Psychology, 2023)
Addressing comorbidities contributing to cognitive impairment in people living with HIV (PLWH) remains imperative. Prior studies utilizing reaction time intra-individual variability (RT-IIV), a robust behavioral marker of cognitive dysfunction, demonstrate increased cognitive impairment in adults living with HIV who have high early life stress (ELS) exposure relative to those with low-ELS exposure. Yet, it is unknown whether RT-IIV elevations are due to high-ELS alone or both HIV-status and high-ELS. In the current study, we explore the potential additive effects of HIV and high-ELS exposure on RT-IIV to better characterize the independent and combined effects of these factors on RT-IIV among PLWH. We assessed 59 PLWH and 69 HIV-negative healthy control (HC) participants with either low or high ELS on RT-IIV during a working memory task (1-back). We observed a significant interaction between HIV status and ELS exposure on RT-IIV, PLWH who had experienced high ELS demonstrating RT-IIV elevations relative to all other groups. In addition, RT-IIV was significantly associated with ELS exposure in PLWH, but not in the HC group. We also observed associations between RT-IIV and measures of HIV-disease severity (plasma HIV viral load, nadir CD4) among PLWH. Taken as a whole, these findings provide novel evidence of the combined effects of HIV and high-ELS exposure on RT-IIV, and thus suggest HIV-related and ELS-related neural abnormalities may act in an additive or synergistic manner to affect cognition. Such data warrant further investigation into the neurobiological mechanisms associated with HIV and high-ELS exposure that contribute to increased neurocognitive dysfunction among PLWH.